APPARENT DIGESTIBILITY OF SELECTED FEED INGREDIENTS IN DIETS FOR MUD CRAB (Scylla paramamosain) - Ketut Suwirya; Nyoman Adiasmara Giri; Muhammad Marzuqi; Sophia Lasma Sagala (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2007)
Cultured mud crabs (Scylla spp.) are commonly fed with ‘trash’ fish. Insufficient supply, high cost and variable quality of ‘trash’ fish has lead to a need to develop costeffective and environmentally friendly formulated diets. This study was conducted to determine quality of selected feed ingredients as protein sources in mud crab diets based on their nutrient composition and digestibility coefficients for dry matter (ADMD), crude protein, lipid and energy. The digestibility coefficients for ADMD ranged from 82.46% to 89.20%. Animal-based feedstuffs such as shrimp head, tiny shrimp and squid liver meal had higher ADMD values than fish meal. Of the plant-based feedstuffs, soy bean meal had the highest ADMD values (89.20%) and corn gluten had the lowest (82.46%). Corn gluten had the lowest protein digestibility (78.81%) and soy bean meal had the highest (96.05%). The lowest energy digestibility (71.13%) was obtained in corn gluten meal. Soy bean meal had a higher energy digestibility value (98.48%) than fish meal (85.95%). All animal meal sources had similar energy digestibility values (85.86%—92.09%).